2020
DOI: 10.21203/rs.3.rs-18069/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recommendations to improve the insurance coverage for physiotherapy services in Iran A multi-criteria decision making approach

Abstract: Background High rate of traffic injuries, climate changes, natural disasters, aging, and chronic diseases have been resulted in a considerable demand for receiving physiotherapy in Iran. However, there are various complications in utilization of physiotherapy services, especially poor insurance coverage. This study investigated and prioritized potential policy recommendations to improve the insurance coverage for physiotherapy services in Iran. Methods The present project was carried out using mix-method (qual… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…According to some studies, it is almost impossible to perform completely consistent pairwise comparisons in the AHP method if there are more than nine criteria; this is often overcome by dividing the criteria into sub-criteria [43,44]. AHP has already been applied in various fields, including marketing, research and development project selection and resource allocation, logistics, transportation, and other decision-making contexts [45][46][47][48][49][50]. For instance, Alossta et al solved the optimal location selection problem through the combined AHP method [51].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some studies, it is almost impossible to perform completely consistent pairwise comparisons in the AHP method if there are more than nine criteria; this is often overcome by dividing the criteria into sub-criteria [43,44]. AHP has already been applied in various fields, including marketing, research and development project selection and resource allocation, logistics, transportation, and other decision-making contexts [45][46][47][48][49][50]. For instance, Alossta et al solved the optimal location selection problem through the combined AHP method [51].…”
Section: Open Accessmentioning
confidence: 99%
“…The technique was also used in health care and medical decision-making. The usefulness of AHP to support group decisions in the medical and health care domains has been established in several previous studies [ 48 , 52 , 53 ]. The results of a systematic review indicated that AHP is a promising support method for shared decision-making between patients and physicians, evaluation and selection of diagnoses and treatments, development of clinical guidelines, and evaluation and prioritizing of health care policies and technologies [ 54 ].…”
Section: Introductionmentioning
confidence: 99%